Physical demands of ball possession games in relation to the most demanding passages of a competitive match - Martin-Garcia, A.; Castellano, J.; Mendez-Villanueva, A.; Diaz, A.; Cos, F.; Casamichana, D. (Journal of Sports Science & Medicine, 2020)
The main aim of this study was to determine the physical demands of different small-sided ball possession games (SSBPGs) according to player field position and compare these demands in relation to the most demanding passages of play (MDP) in competitive matches. Global positioning system data were obtained from 25 football players (20.4 ± 2.1 yrs, 1.78 ± 0.66 m, 69.7 ± 6.1 kg) belonging to the reserve squad of a Spanish La Liga Club. Players were categorized according to positional groups; full back (FB), central defender (CD), midfielder (MF), wide midfielder (WMF) and forwards (FW). The variables analyzed were relativized to metres per minute (m·min-1): total distance covered (TD), TD at high speed (HSR; >19.8 km·h-1), TD at sprint (SPR; >25.2 km·h-1), the number of accelerations (ACC) and decelerations (DEC) at high intensity (> +/-3 m·s-2), the average metabolic power (AMP; W·kg-1) and the high metabolic load distance (HMLD; >25.5 W·kg-1). The MDP were analyzed using a rolling average method, where maximal values were calculated for 3 and 5 minutes to compare with SSBPGs using AMP as a criterion variable. The results were obtained from the SSBPGs relative to the MDP (expressed in %) for each player position. FB showed the greatest magnitude of overload in ACC/DEC according to the MDP in the two smaller SSBPGs formats (201-217%), whereas MF showed lower values (105-140%). The load expressed in relation to the MDP can be different depending on the format of the SSBPGs and the characteristics of playing position. These factors should be considered by the coaches when planning training. Key Points